Simulate the impact of natural disaster on automobile supply chains - Ang, Lin Giat (2012)
The recent disaster affecting the global supply chain has raised the awareness for management to review their supply chain strategy. Performance of the automaker company aftermath of disaster is the biggest concern in this study. An automaker manufacturing plant basic model is developed and series of simulation data are inputted. Factors such as disaster probability, inventory delivery lead time and inventory holding level which associate with the company to be resilient are identified through model simulation. The simulation shows how these factors associate with the supply chain and disaster destructive level. 19 simulation tests with different value of variables are carried on. Thus, quantity of completed order, rejected order, total customer order is being recorded. The percentage of completed order serves as an index in analyzing automaker performance. Supply chain responsiveness, frequency of occurrence of disaster and inventory level is the most important indicators in affecting company performance. Few suggestions for future supply chain to be resilient relating with each term are suggested.